Nitric Oxide Block of Outward-Rectifying K(+) Channels Indicates Direct Control by Protein Nitrosylation in Guard Cells - Sokolovski, Sergei (American Society of Plant Biologists, 2004)
Recent work has indicated that nitric oxide (NO) and its synthesis are important elements of signal cascades in plant pathogen defense and are a prerequisite for drought and abscisic acid responses in Arabidopsis (Arabidopsis thaliana) and Vicia faba guard cells. Nonetheless, its mechanism(s) of action has not been well defined. NO regulates inward-rectifying K(+) channels of Vicia guard cells through its action on Ca(2+) release from intercellular Ca(2+) stores, but alternative pathways are indicated for its action on the outward-rectifying K(+) channels (I(K,out)), which are Ca(2+) insensitive. We report here that NO affects I(K,out) when NO is elevated above approximately 10 to 20 nm. NO action on I(K,out) was consistent with oxidative stress and was suppressed by several reducing agents, the most effective being British anti-Lewisite (2,3-dimercapto-1-propanol). The effect of NO on the K(+) channel was mimicked by phenylarsine oxide, an oxidizing agent that cross-links vicinal thiols. Neither intracellular pH buffering nor the phosphotyrosine kinase antagonist genistein affected NO action on I(K,out), indicating that changes in cytosolic pH and tyrosine phosphorylation are unlikely to contribute to NO or phenylarsine oxide action in this instance. Instead, our results strongly suggest that NO directly modifies the K(+) channel or a closely associated regulatory protein, probably by nitrosylation of cysteine sulfhydryl groups.